Globalization : the human consequences - Bauman, Zygmunt (New York : Columbia University Press, 1998)
This book is about: Time and Class; Space Wars; Tourists and Vagabonds; Global Law; Local Orders.
Keywords: Social aspects; Postmodernism; Internationalism; Postmodernism -- Social aspects; Freedom of movement; Social -- Mobility; International economic relations